ACCOUNT OPTIONS ON THE DISTRIBUTION CORRESPONDING RESULT COMMERCIAL BUILDING CONTRACTS FROM PUBLIC INSTITUTIONS IN ROMANIA - Cristina Otilia, TENOVICI (Strategii Manageriale)
Primary issue in accounting for construction contracts is the recognition of revenue and contract costs of those reporting periods in which the work was performed, hence the outcome of the contract for construction. Date, or where completion of a construction contract can be found in different reporting periods. The question concerns the date on which the recognized result. Option appears to recognize the result as a sum of partial results for each of the years covered by the contract duration or it will recognize the completion of the construction contract.